HE GENERA BELOTIA Rich. AND TRICHOSPERMUM Bl. (Tiliaceae) - A.J.G.H Kostermans (REINWARDTIA, 1962)
The genus Belotia was founded in 1845 by A. Richard (in R. de la liagra, Hist. Cuba, Bot. 1: 207), based on a single species: B. grewiifolia; liichard added Grewia mexicana DC. (1824) as a synonym.Sprague (in Kew Bull. 1921: 270-278) wrote a monograph on the knus. He characterized Belotia as follows: Presence of nectaries at the Itase of the petals and their absence on the androgynophore; the blue or Inlet, rarely white petals, the bilocular ovary with pluriovulate loculi; the a– culicidal capsule, strongly compressed transversally to the septum and a–ediscoid ciliate seeds. He than adds: "In all these respects Belotia resem-Ihles the Old-World genus Trichospermum, which differs in having a pair of I nectaries at the base of the lamina, and a pseudo- umbellate inflorescence".The differences are consequently very small and since I found that le laminal nectaries occur only occasionally in one species of Tricho-tpermmn (javanicuvi), it becomes debatable, whether the inflorescence character is of such importance as to keep both genera apart.Burret (in Notizbl. bot. Garten Berlin 9: 603. 1927) keys out Belotia against Trichospermum in the following way: Trichospermum with 25-50 ovules,irregularly placed, as against Belotia with 12-16 ovules per locule in two regular rows; inflorescences in the former axillary and bi-or pluri-chasial,in Belotia axillary and terminal panicles.Furthermore he adds: fruit with 2, rarely 3 cells Trichospermum is to the 2-3 celled fruit in Belotia; this- of course -is a differential character of little or no value. Burret does not mention at all the laminal nectaries; according to him (p. 855) the number of ovules and their placentation should be the main differential character.I had at my disposal far more material of Trichospermum than Burret and could examine numerous young fruit,where the number of ovules and their placentation may be easily observed.